砂轮性能对齿轮磨削效率及磨削烧伤的影响 - 肖伟敬; 汪军; 付慰平; 敖宝林; 丁英晖 (Jixie chuandong)
For improving the grinding efficiency and reducing the probability of gear grinding burns in the process of the gear grinding,the gear grinding experiment is carried out through changing grinding wheel type based on knowing the machine performance.The influence factor of grinding wheel on grinding efficiency is summarized through the comparing the grinding results of the three kinds of grinding wheel,the best kind of grinding wheel suitable for the gear containing different material is found and applied it in the practice.The conflict of the grinding efficiency and grinding burn is solved.